Unlocking value from machines: business models and the industrial internet of things. Issue 1 (2nd January 2017) - Ehret, Michael; Wirtz, Jochen
ABSTRACT: In this article, we argue that the Industrial Internet of Things (IIoT) offers new opportunities and harbours threats that companies are not able to address with existing business models. Entrepreneurship and Transaction Cost Theories are used to explore the conditions for designing nonownership business models for the emerging IIoT with its implications for sharing uncertain opportunities and downsides, and for transforming these uncertainties into business opportunities. Nonownership contracts are introduced as the basis for business model design and are proposed as an architecture for the productive sharing of uncertainties in IIoT manufacturing networks. The following three main types of IIoT-enabled business models were identified: (1) Provision of manufacturing assets, maintenance and repair, and their operation, (2) innovative information and analytical services that help manufacturing (e.g. based on artificial intelligence (AI), big data, and analytics), and (3) new services targeted at end users (e.g. offering efficient customisation by integrating end users into the manufacturing and supply chain ecosystem).